Real‐world effectiveness of adalimumab in patients with moderate‐to‐severe hidradenitis suppurativa: the 1‐year SOLACE study. (25th August 2021) - Gulliver, W.; Alavi, A.; Wiseman, M.C.; Gooderham, M.J.; Rao, J.; Alam, M.S.; Papp, K.A.; Desjardins, O.; Jean, C.
Abstract: Background: Long‐term, real‐word data are needed to help manage patients with hidradenitis suppurativa (HS) through this recurrent, painful and debilitating disease. Objectives: To primarily measure real‐world effectiveness of adalimumab in HS and to secondarily observe clinical course of HS in the light of patients' response. Methods: In SOLACE, adults with moderate‐to‐severe HS in need for change in ongoing therapy were treated with adalimumab for up to 52 weeks as per physician's medical practice. Treatment effectiveness was measured by Hidradenitis Suppurativa Clinical Response (HiSCR). Inflammatory nodules, abscesses and draining fistulas were counted, Hurley stage was assessed, and disease severity was rated using the International HS Severity Scoring System (IHS4). A post hoc analysis further explored the HiSCR response by abscess and inflammatory nodule (AN) count at baseline (low, medium and high) and gender. Spontaneously reported safety events were collected. Results: From 23 Canadian centres, 69% of the 138 patients achieved HiSCR at week 24, which increased to 82% and 75% at week 52 in patients with medium and high AN counts, respectively. Gender (4 times the odds for female) and age at HS onset (5% decrease with each additional year) had an effect on achieving HiSCR. Treatment with adalimumab led to an important decrease in number of lesions in responders, with most gains observed in inflammatory nodules, more frequently in the lower body area of patients in the high AN count group. The IHS4 scores of responders were substantially lowered, with a larger decrease in patients of the high AN count group. No new safety signal was detected. Conclusions: The effectiveness of adalimumab was maintained during this 1‐year period, and an optimal gain was documented for patients with medium and high AN counts. These real‐world data support a prompt treatment of HS patients and the use of IHS4 to monitor treatment.